Cardiac damage in an adolescent patient with COVID-19: a case report - Pujowaskito, Prihati; Tartila, Tamia S; Tafriend, Novaro A; Jannah, Fatimah D K; Mayasari, Elsy (ACTA Medical Health Sciences, 2022)
COVID-19 has been found to affect the cardiovascular system leading to myocardial damage. A study of 41 patients in Wuhan, China, found that 12% of COVID-19 patients experienced virus-related acute cardiac damage.Subsequent bigger Chinese studies also found acute cardiac damage in 7.2% to 27.8% of hospitalized patients. As a chronicsequela, this condition may result in cardiomyopathy. We report acase of an adolescent COVID-19 survivor with dilated cardiomyopathy with no underlying heart disease. A male patient aged 16 years old was admitted to our outpatient clinic with the primary symptom of exhaustion and had recovered frommild to moderate COVID-19 one month prior to the visit. No previous history of heart disease was documented. Physical examination showed no abnormalities. Laboratory results revealed substantially elevated NT-proBNP (7705 pg/mL) and D-dimer (1850 ng/mL). ECG presented normal sinus rhythm with poorR wave progression. Echocardiography revealed all chamber dilatation, eccentric left ventricular hypertrophy, globalhypokinetic, moderate mitral regurgitation, and reduced ejection fraction (22%). We diagnosed the patient with new-onset dilated cardiomyopathy and began treatment with candesartan, bisoprolol, furosemide, spironolactone, rivaroxaban, and trimetazidine. The recovery was steady at three-month follow-up visit. The emergence of new-onset cardiomyopathy in this previously healthy adolescent raisesthepossibility of COVID-19 acting asthe sole cause of myocardial injuryin the absence of underlying heart disease. To avoid further complications, comprehensive evaluation and effective therapy should be implemented during hospitalization and post-discharge. Additional tests such as cardiac magnetic resonance imaging and endomyocardial biopsies shouldbe performed to support final proof. DOI : 10.35990/amhs.v1n2.p88-96 REFERENCES Huang C, Wang Y, Li X, Ren L, Zhao J, Hu Y, et al. Clinical features of patients infected with 2019 novel coronavirus in Wuhan, China. Lancet. 2020;395:497–506. https://doi.org/10.1016/S0140-6736(20)30183-5 World Health Organization. COVID-19 weekly epidemiological update [updated 22 March 2022; cited 22 March 2022]. Available from: https://www.who.int/docs/default-source/coronaviruse/situation-reports/20220322_weekly_epi_update_84.pdf?sfvrsn=9ec904fc_4&download=true Tosepu R, Effendy DS, Ahmad LOAI. The first confirmed cases of COVID-19 in Indonesian citizens. Public Health of Indonesia. 2020;6(2):70–71. https://doi.org/10.36685/phi.v6i2.337 Indonesian Ministry of Health. COVID-19 situation in Indonesia [updated 22 March 2022; cited 22 March 2022]. Available from: https://covid19.go.id/artikel/2022/03/22/situasi-covid-19-di-indonesia-pdate-22-maret-2022 Mesquita RR, Junior LCFS, Santana FMS, Oliveira TF, Alcantara RC, Arnozo GM, et al. Clinical manifestations of COVID-19 in the general population: systematic review. Wien Klin Wochenschr. 2021;133:377–382. https://doi.org/10.1007/s00508-020-01760-4 Hendren NS, Drazner MH, Bozkurt B, Cooper LT. Description and proposed management of the acute COVID-19 cardiovascular syndrome. Circulation. 2020;141(23):1903–1914. https://doi.org/10.1161/CIRCULATIONAHA.120.047349 Wang D, Hu B, Hu C, Zhu F, Liu X, Zhang J, et al. Clinical characteristics of 138 hospitalized patients with 2019 novel coronavirus-infected pneumonia in Wuhan, China. JAMA. 2020;323(11):1061–1069. https://doi.org/10.1001/jama.2020.1585 Shi S, Qin M, Shen B, Cai Y, Liu T, Yang F, et al. Association of cardiac injury with mortality in hospitalized patients with COVID-19 in Wuhan, China. JAMA Cardiol. 2020;5(7):802–810. https://doi.org/10.1001/jamacardio.2020.0950 Guo T, Fan Y, Chen M, Wu X, Zhang L, He T, et al. Cardiovascular implications of fatal outcomes of patients with coronavirus disease 2019 (COVID-19). JAMA Cardiol. 2020;5(7):811–818. https://doi.org/10.1001/jamacardio.2020.1017 Zaman S, MacIsaac AI, Jennings GLR, Schlaich MP, Inglis SC, Arnold R, et al. Cardiovascular disease and COVID-19: Australian and New Zealand consensus statement. Med J Aust. 2020;213(4):182–187. https://doi.org/10.5694/mja2.50714 Limongelli G, Crotti L. COVID-19 pandemia and inherited cardiomyopathies and channelopathies: a short-term and long-term perspective. Orphanet J Rare Dis. 2020;15:157. https://doi.org/10.1186/s13023-020-01444-2 Fried JA, Ramasubbu K, Bhatt R, Topkara VK, Clerkin KJ, Horn E, et al. The variety of cardiovascular presentations of COVID-19. Circulation. 2020;141:1930–1936. https://doi.org/10.1161/CIRCULATIONAHA.120.047164 Driggin E, Madhavan MV, Bikdeli B, Chuich T, Laracy J, Biondi-Zoccai G, et al. Cardiovascular considerations for patients, health care workers, and health systems during the COVID-19 pandemic. J Am Coll Cardiol. 2020;75:2352–2371. https://doi.org/10.1016/j.jacc.2020.03.031 Schilling JD, Ravichandran AK, Mandras SA. Management of the hospitalized COVID-19 patient with acute cardiomyopathy or heart failure [updated 16 April 2020; cited 23 March 2022]. Available from: https://www.acc.org/latest-in-cardiology/articles/2020/04/16/14/42/management-of-the-hospitalized-covid-19-coronavirus-2019-patient-with-acute-cardiomyopathy-or-heart-failure Kang Y, Chen T, Mui D, Ferrari V, Jagasia D, Scherrer-Crosbie M, et al. Cardiovascular manifestations and treatment considerations in COVID-19. Heart. 2020;106:1132–1141. http://dx.doi.org/10.1136/heartjnl-2020-317056 Sukmawan R. Cardiomyopathy in COVID-19 survivors: mechanism, management, and prevention. Indonesian J Cardiol. 2020;41:120–124. https://doi.org/10.30701/ijc.1012 Herman DS, Lam L, Taylor MR, Wang L, Teekakirikul P, Christodoulou D, et al. Truncations of titin causing dilated cardiomyopathy. N Engl J Med. 2012;366:619–628. https://doi.org/10.1056/nejmoa1110186 Pinamonti B, Abate E, de Luca A, Finocchiaro G, Korcova R. Role of cardiac imaging: echocardiography. In: Sinagra G, Merlo M, Pinamonti B, editors. Dilated cardiomyopathy: from genetics to clinical management. Cham (CH): Springer; 2019. https://doi.org/10.1007/978-3-030-13864-6_7 European Society of Cardiology. European Society of Cardiology guidance for the diagnosis and management of cardiovascular disease during the COVID-19 pandemic: part 1 – epidemiology, pathophysiology, and diagnosis. Eur Heart J. 2022;43:1033–1058. https://doi.org/10.1093/eurheartj/ehab696 Ni W, Yang X, Yang D, Bao J, Li R, Xiao Y, et al. Role of angiotensin-converting enzyme 2 (ACE2) in COVID-19. Crit Care. 2020;24:422. https://doi.org/10.1186/s13054-020-03120-0 Yang G, Tan Z, Zhou L, Yang M, Peng L, Liu J, et al. Effects of angiotensin II receptor blockers and ACE inhibitors on virus infection, inflammatory status, and clinical outcomes in patients with COVID-19 and hypertension: a single-center retrospective study. Hypertension. 2020;76(1):51–58. https://doi.org/10.1161/hypertensionaha.120.15143 COVID-19 RISk and Treatments (CORIST) Collaboration. RAAS inhibitors are not associated with mortality in COVID-19 patients: findings from an observational multicenter study in Italy and a meta-analysis of 19 studies. Vascul Pharmacol. 2020;135:106805. https://doi.org/10.1016/j.vph.2020.106805 European Society of Cardiology. ESC guidance for the diagnosis and management of cardiovascular disease during the COVID-19 pandemic: part 2 – care pathways, treatment, and follow-up. Eur Heart J. 2022;43:1059–1103. https://doi.org/10.1093/eurheartj/ehab697 Tang N, Bai H, Chen X, Gong J, Li D, Sun Z. Anticoagulant treatment is associated with decreased mortality in severe coronavirus disease 2019 patients with coagulopathy. J Thromb Haemost. 2020;18:1094–1099. https://doi.org/10.1111/jth.14817 Ramacciotti E, Agati LB, Calderaro D, Aguiar VCR, Spyropoulos AC, de Oliveira CCC, et al. Rivaroxaban versus no anticoagulation for post-discharge thromboprophylaxis after hospitalisation for COVID-19 (MICHELLE): an open-label, multicentre, randomised, controlled trial. Lancet. 2022;399:50–59. https://doi.org/10.1016/S0140-6736(21)02392-8 Al-kuraishy HM, Al-Gareeb AI, Welson NN, Batiha GES. Trimetazidine and COVID-19-induced acute cardiac injury: a missed key. Int J Clin Pharm. 2022;44:832–833. https://doi.org/10.1007/s11096-022-01408-5